Inspiring Trends in Medical Education: Emphasizing Community-Based and Community-Oriented Approaches - Salam, Abdus; Islam, Sharmin; Hassan, Abu; Mohd Taibi, Muhd Khairi Bin; Al Mahmood, Abu Kholdun (International Journal of Human and Health Sciences (IJHHS), 2025)
Abstract not available International Journal of Human and Health Sciences Vol. 09 No. 01 Jan’25 Page: 3-6